Prevalence and Risk Factors of Parasitic Infections among Children in Kamrangirchar Slum, Dhaka, Bangladesh (Bangladesh Journal of Zoology, 2025)
A cross-sectional survey was conducted to determine the prevalence of intestinal parasitic infections and identify the risk factors among 80 children, aged 0–15 years, who lived in a slum. A sample size of eighty (80) participants was used for the investigation. A structured questionnaire and anthropometric tools were used to identify epidemiological data and risk factors. Stool samples were collected from the children and were subjected to laboratory analysis using the formol-ether concentration technique. The result revealed a high prevalence of intestinal parasitic infections, with an overall prevalence of 80%. Helminths presented a more significant prevalence than protozoans. Ascaris lumbricoides (40%) was the most prevalent parasite, followed by Trichuris trichiura (30.00%), Giardia duodenalis (20.00%), Hymenolepis nana (12.50%), Entamoeba histolytica (10.00%), Taenia sp. Ancylostoma duodenale (7.50%) and Escherichia coli (2.50%). The probability of parasitic infection was higher in boys than girls (p-value= 0.1569, 95% CI 0.72-6.7). The highest infection rate (94.12%) was detected in children in the age group 8-11years, and the least infection rate (33.33%) was detected in the age group 0-3years; additionally, statistical analysis revealed a statistically significant difference between intestinal parasite infections concerning age groups (p- value= 0.0043). 100% prevalence was recorded during the summer season, while 60% prevalence was found in autumn (p value= 0.0003). The study findings showed that illiteracy, poor hygiene practices, drinking water source, house and latrine type, and deworming treatment were the factors associated with intestinal parasitic infections. Increased hygiene practices, poverty reduction, and deworming promotions are essential to reduce intestinal parasitic infections among slum children. Mass-scale awareness camping could be effective as well.Bangladesh J. Zool. 53(2): 158-169, 2025